Orbital abscess following posterior subtenon injection of triamcinolone acetonide. (4th May 2017) - Rhatigan, Maedbh; McAnena, Lisa; McElnea, Elizabeth; Connell, Paul; Fulcher, Tim
ABSTRACT: Orbital cellulitis is a serious sight threatening and potentially life threatening condition which can be complicated by orbital abscess formation. Posterior subtenon (PST) injection of corticosteroid is commonly used in the treatment of posterior segment inflammation including post-operative macular oedema. We report a case of orbital abscess formation as a late complication of PST triamcinolone acetonide and discuss the presentation, diagnosis and management.